Henning Koch og Kristian Hvidt (udg.): Danmarks Riges Grundlove 1849-1866-1915-1953 parallel opsætning. (Chr. Ejlers’ Forlag, 1999). 116 s., 120 kr. - Strange Petersen, Erik (Historie/Jyske Samlinger, 2000)
-